Characterization of Decent Work in Medellin and other Main Cities of Colombia (2010-2018) - Lopez Mera, Silvio Fernando (Universidad Pedagógica y Tecnológica de Colombia, 2020)
International Labor Organization (ILO), taking into account the transformations, problems, new relationships and dynamics that occurred in employment, proposed in the last decade of the 20th century a novel concept on employment: decent work. Based on the 2010-2018 Great Integrated Household Survey (GEIH by its acronym in Spanish) of the National Administrative Department of Statistics (DANE, by its acronym in Spanish), the base RLDatos of occupational risks of Fasecolda and the Sislab of Escuela Nacional Sindical (ENS), this paper estimates the employment for the national added value, for Medellin and other important cities of the country, and a series of labor indicators within the framework of the dimensions of decent work proposed by the ILO. The results indicate that, although the country has made progress in terms of decent employment, it has been insufficient, so there is still a long way to conceive employment in Colombia as decent. In the same way, important differences between territories are evident.